Ideas From Bounded Confidence Theory Applied to Dynamical Networks of Interacting Free-Bodies - O'Keeffe, Gary J.; Dassios, Ioannis K. (Frontiers in Physics, 2019)
An approximation method is introduced for simulating the motion of interacting free-bodies. Concepts from bounded confidence theory (in network science) and asymptotic analysis (in physics) are combined to create the method. This method can reduce the computational load required to simulate the dynamics of free-bodies. A case study is presented and a range of parameter values are explored to analyze the methods performance.